2010
DOI: 10.1242/jcs.060723
|View full text |Cite
|
Sign up to set email alerts
|

Charged residues in the C-terminus of the P2Y1 receptor constitute a basolateral-sorting signal

Abstract: SummaryThe P2Y 1 receptor is localized to the basolateral membrane of polarized Madin-Darby canine kidney (MDCK) cells. In the present study, we identified a 25-residue region within the C-terminal tail (C-tail) of the P2Y 1 receptor that directs basolateral sorting. Deletion of this sorting signal caused redirection of the receptor to the apical membrane, indicating that the region from the N-terminus to transmembrane domain 7 (TM7) contains an apical-sorting signal that is overridden by a dominant basolatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…These studies point out the important role of charged amino acid residues in the NH 2 terminus of NBCe1 in its accurate targeting to the plasma membrane. The role of charged amino acid moieties in the targeting of other proteins such as P2Y1 receptor to the membrane has been documented (40). The results presented in the present study and those describing the role of charged amino acids in the targeting of other membrane bound proteins suggest that such amino acid residues are important determi- (22,40).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…These studies point out the important role of charged amino acid residues in the NH 2 terminus of NBCe1 in its accurate targeting to the plasma membrane. The role of charged amino acid moieties in the targeting of other proteins such as P2Y1 receptor to the membrane has been documented (40). The results presented in the present study and those describing the role of charged amino acids in the targeting of other membrane bound proteins suggest that such amino acid residues are important determi- (22,40).…”
Section: Discussionsupporting
confidence: 52%
“…Charged amino acid residues have been shown to play a role in the targeting of membrane bound proteins (40). To determine the role of the negative charge of aspartic acid residues 405 and 416 in the targeting of NBCe1A to the basolateral membrane, we examined the effect of their replacement with glutamic acid.…”
Section: Mutations D449a and D460a In Nbce1b Lead To Its Retention Inmentioning
confidence: 99%
“…R124 is the only charged residue in IL-2 that is essential for NIS targeting to the cell surface Intracellularly facing charged residues have been shown to be important in trafficking of membrane proteins (Kasahara et al, 2004;Li et al, 2012;Wolff et al, 2010). IL-2 contains three basic (R111, R124, R127) and two acid residues (E119, E122).…”
Section: R124h Nis Is Intracellularly Retainedmentioning
confidence: 99%
“…3C). These results suggest that P570-Q587 and particularly P582-Q587 is critical in basolateral targeting of the P2X 7 R. Interestingly, a recent study has reported basolateral targeting of the ATP-sensitive metabotropic P2Y1 receptor that is also independent of l1B but critically requires a stretch of 25 residues in the distal intracellular C-terminus [14]. The findings from previous and present studies suggest that the receptors for extracellular ATP are directed to the basolateral membranes via motifs that are distinct from those previously identified [7].…”
Section: Discussionmentioning
confidence: 82%
“…Clearly, our results are consistent with these studies. The C-terminal part of this microdomain (P582-Y595) possesses a canonical basolateral targeting motif YxxU [7,14] (Y588-S589-G590-F591) (Fig. 3A).…”
Section: Discussionmentioning
confidence: 99%